Public finances in Romania during and after the economic crisis 2008-2009 - CÂMPEAN, Stelian Dan (Progress in Economic Sciences; No 2 (2015): Progress in Economic SciencesDO - 10.14595/PES/02/011, 2015)
The aim of this article is to present Romania’s problems and solutions during and after the economic crisis of 2008-2009. The paper starts with the definitions of public finances and economic crisis and also a brief description of Romania’s economy, continuing with a deeper analysis of the determinants and symptoms of the recession in the country, as well as the perspectives for further development. The financial assessment of Romania’s situation in the broader EU context can be understood by looking at the GDP and the country’s economic activities in relation to it, and by reviewing the information supplied by the National Bank of Romania and others institutions and selected literature. The article is complemented by author’s opinions.